2020
DOI: 10.1590/2177-6709.25.2.061-068.oar
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular and temporomandibular morphologic characteristics of patients with suspected unilateral condylar hyperplasia: a CT study

Abstract: Introduction: Facial asymmetry associated with unilateral condylar hyperplasia (UCH) is a complicated clinical condition. Objective: The objective of this study was to describe morphological characteristics of the mandible and the temporomandibular joint in patients with facial asymmetry, using computed tomography and 3D reconstruction. Methods: A retrospective observational study was performed with patients displaying facial asymmetry evaluated by single photon emission computed tomography (SPECT)/CT anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…CT imaging aids in multiplanar imaging of the condyles 22 . A recently conducted retrospective CT based study revealed a significant increase in condylar length and other dimensions on the hyperplastic side when compared to the normal side 23 . CH characteristically appears as a uniform enlargement of the condylar head 19 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…CT imaging aids in multiplanar imaging of the condyles 22 . A recently conducted retrospective CT based study revealed a significant increase in condylar length and other dimensions on the hyperplastic side when compared to the normal side 23 . CH characteristically appears as a uniform enlargement of the condylar head 19 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in the present study, when the values are analyzed by affected side and by each entity, with the exception of GFA, all joint spaces were smaller. It was even evident in cases of condylar hyperplasia, in which there is a substantial change in the condylar size and the height of the joint cavity towards the affected side [ 31 ]. It was evidenced that the joint spaces were decreased with respect to the non-asymmetric subjects and only for the posterior joint space it was not significant in HH.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 CH can be broadly classified into three types: hemimandibular hyperplasia, in which the vertical lengths of the mandibular condyle and ramus increase; hemimandibular elongation, in which the horizontal lengths of the mandibular condyle and ramus increase; or a hybrid form. [9][10][11] In the hybrid form, there is a combination of the 2 vectors, with a resultant severe expression of the pathology. If the unilateral mandibular condyle increases in length vertically, canting-type facial asymmetry occurs.…”
Section: Introductionmentioning
confidence: 99%